Depression in independent young adults on the autism spectrum: Demographic characteristics, service use, and barriers. (October 2021) - Zheng, Shuting; Adams, Ryan; Taylor, Julie Lounds; Pezzimenti, Florencia; Bishop, Somer L
Depression is a common problem for adults on the autism spectrum, but little is known about depression-related service receipt in this group. To understand depression diagnostic and treatment status better, we collected information on current depressive symptoms, depression diagnosis, and treatment status of 315 young adults with a childhood diagnosis of autism from the Simons Foundation Powering Autism Research for Knowledge registry. About two-thirds (65.4%) of the adults had been diagnosed with depression, and 46.7% currently met clinical cut-offs for depression on depressive symptoms measures. Among the currently depressed, the majority (83.0%) had a formal depression diagnosis. Despite being no more likely than males to be currently depressed, females (biological sex) were more likely to have received a depression diagnosis. As for depression treatment, 58.5% of currently depressed adults were currently being treated, and 68% had previously received treatment. Medication was the most common form of treatment, followed by individual therapy. Likelihood of receiving depression treatment was higher among those with a formal depression diagnosis and with higher levels of education. Adults reported several barriers to accessing treatment for depression, including financial and insurance issues, accessibility to appropriate care, and professionals' lack of understanding about depression in autism. Lay abstract: Depression is common among adults on the autism spectrum, but little is known about the extent to which these adults living in the community access diagnostic and treatment services for depression. To address this gap, we surveyed 315 adults on the autism spectrum on depression symptoms, diagnosis, and services. About half of the sample had scores on standard depression measures that suggested they were currently depressed ( n = 147, 46.7%). Among the currently depressed, most of them had received a depression diagnosis from a professional. Depressed females were about 3.5 times more likely than depressed males to have a depression diagnosis. More than half of the currently depressed adults on the autism spectrum reported receiving depression treatment at the time of the study, while about two-thirds had previously received treatment. Those with a depression diagnosis were more likely to have received treatment, and those who had some education beyond high school were more likely to be currently receiving treatment. Financial and insurance issues were the most common barriers that adults reported in accessing treatment for depression.